IMPLEMENTASI STRATEGI BERBASIS MULTIPLE INTELLIGENCES PADA KEGIATAN PEMBELAJARAN EKSTRAKULIKULER DI MTs UMMUSSHABRI KENDARI - La Hadisi (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2015)
Abstract The concept of multiple intelligences which is focused on the uniqueness isalways find the advantages of each child. The Purpose of this study is find out the Implementation of learning strategy in multiple intelligences practiced in Madrasah Tsanawiyah Ummusshabri, Kendari. The results indicate some facts: 1) the basic implementation of learning strategy base on multiple intelligences are orientation, content and curriculum development of KTSP; 2) the conceptual framework of multiple intelligence implementation includes three stages: the input stage, which is identification of intelligence, learning process using that multiple intelligences that includes eight intelligences, the output stage byconduct ssessment that covering three domains: cognitive, affective andpsychomotor; 3) the advantages of learning strategy using multiple intelligences has been adapted to the abilities and intelligence students, so students are always enthusiastic and prevent them to get bored learning. However, the weaknesses ofthe strategy lies on the extra-curricular curriculum has not been fix as a reference by teachers in planning the learning proces. Key Words: Curriculum Implementation, Learning Strategies, MultipleIntelligences  AbstrakKonsep  multiple  intelligences yang menitik beratkan pada ranah keunikan selalu menemukan kelebihan setiap anak. Penelitian ini bertujuan untuk mengetahui implementasi strategi pembelajaran multiplle intelligences  di Madrasah Tsanawiyah Ummusshabri Kendari. Hasil  penelitian  menunjukkan: 1)  Dasar implementasi strategi pembelajaran berbasis multiple intelligences adalah orientasi, isi dan pengembangan kurikulum KTSP  2) Kerangka konseptual  implementasi  multiple intelligences  meliputi 3 tahap yaitu: tahap input yang merupakan identifikasi kecerdasan, tahap proses dengan pembelajaran yang menggunakan strategi multiple intelligences yang mencakup 8 kecerdasan, tahap output dengan menyelenggarakan penilaian yang meliputi tiga ranah: kognitif, afektif dan psikomotorik; 3) Kelebihan strategi pembelajaran multiple intelligences dari segi proses sudah disesuaikan dengan kemampuan dan kecerdasan siswa, sehingga para siswa selalu antusias dan tidak bosan serta jenuh dalam mengikuti kegiatan pembelajaran. Adapun kekurangannya terletak pada penyediaan kurikulum ekstra kurikuler belum paten untuk   dijadikan acuan oleh guru-guru dalam merencanakan proses pembelajaran.Kata Kunci : Impementasi kurikulum, Strategi Pembelajaran, Multiple Intelligences